Prenatal diagnosis and gonadal findings in X/XXX mosaicism. Issue 2 (April 1977) - Kohn, G; Cohen, M M; Beyth, Y; Ornoy, A
Abstract : Prenatal diagnosis of a case of X/XXX mosaicism is presented. In spite of the fact that over 50% of the cells cultured from both ovaries were trisomic for the X chromosome, fetal öocytes were rarely found. This case illustrates that the presence of a triple-X cell line, even in a relatively high percentage of ovarian cells, does not necessarily protect the ovary from 'aöogenesis'. This observation might prove useful in the counselling of future cases involving the prenatal detection of sex chromosome mosaicism.